Synthesis and characterization of 2, 2′-bithiophene end-capped dihexyloxy phenylene pentamer and its application in a solution-processed organic ultraviolet photodetector. Issue 66 (28th June 2016) - Lim, Lih Wei; Teh, Chin Hoong; Daik, Rusli; Sarih, Norazilawati Muhamad; Mat Teridi, Mohd Asri; Muhammad, Fahmi Fariq; Sulaiman, Khaulah
Abstract : A new solution processable small organic material, 2, 2′-bithiophene end-capped dihexyloxy phenylene (BHBT2 ) was synthesized and applied in organic UV photodetector, resulting the device exhibited fast, reversible and stable response upon detection. Abstract : In this work a new solution processable small organic material, namely 2, 2′-bithiophene end-capped dihexyloxy phenylene pentamer (BHBT2 ) was synthesized, characterized and applied in the fabrication of an organic ultraviolet photodetector. The material was synthesized via Williamson etherification, bromination and Suzuki coupling. FTIR and NMR spectroscopies were recorded forBHBT2 along with its optical, thermal and electrochemical properties. Finally, BHBT2 was used as donor material to produce a solution-processed UV photodetector based on aBHBT2  : PC61 BM organic active layer. Results showed that in forward biasing, the photodetector exhibited a photovoltaic effect with J sc = 1.80 mA, V oc = 0.66 V, FF = 0.30 and PCE = 0.98%, while in reverse biasing, the photodetector exhibited a fast, reversible and stable response with the highest detectivity of 1.47 × 10 9 jones. The realization of efficient UV detection was attributed to the strong absorption ofBHBT2 and PC61 BM in the UV region. Hence, theBHBT2 pentamer coupled with PC61 BM can be considered as a potential material to be applied in a solution-processed organic UV photodetector.